2017
DOI: 10.13037/ras.vol15n54.4632
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Desenvolvimento Neuropsicomotor De Crianças Na Primeira Infância Em Uma Escola De Educação Infantil Do Vale Do Rio Dos Sinos – Rs

Abstract: Introdução: O desenvolvimento infantil é um processo dinâmico que se inicia na vida intrauterina e envolve o crescimento físico, a maturação neurológica e a construção de habilidades comportamentais. Objetivos: Avaliar o desenvolvimento neuropsicomotor de crianças de até 24 meses, matriculadas em uma escola de educação infantil na região do Vale do Rio dos Sinos/RS. Materiais e métodos: Esta pesquisa consistiu em um estudo observacional descritivo com abordagem quantitativa. Participaram desta pesquisa 29 cria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Regarding the screening of childhood NPMD through Denver II, a similar study conducted in the State of Rio Grande do Sul also found language mastery as the most affected area among children (26) . Delays in the child's language development can occur for many reasons, such as parent's poor education, the presence of four or more children living in the same residence, family history of delay, the father working full time, poor quality of communication with the mother, and the fact that the family does not have the habit of reading to the child.…”
Section: Knowledge Of Caregivers and Factors Associated With Neuropsychomotor Development In Childrenmentioning
confidence: 87%
“…Regarding the screening of childhood NPMD through Denver II, a similar study conducted in the State of Rio Grande do Sul also found language mastery as the most affected area among children (26) . Delays in the child's language development can occur for many reasons, such as parent's poor education, the presence of four or more children living in the same residence, family history of delay, the father working full time, poor quality of communication with the mother, and the fact that the family does not have the habit of reading to the child.…”
Section: Knowledge Of Caregivers and Factors Associated With Neuropsychomotor Development In Childrenmentioning
confidence: 87%